Project Based Learning with Loose Parts Improves Preschool Creativity: Pembelajaran Berbasis Proyek dengan Bahan-Bahan Fleksibel Meningkatkan Kreativitas Anak Usia Dini - Agustina Kurniawati; Luluk Iffatur Rocmah (Academia Open, 2025)
General Background: Creativity is a fundamental component of early childhood development that supports cognitive, social, emotional, and problem-solving growth during the formative years. Specific Background: In many preschool settings, learning remains teacher-centered and relies on structured worksheets, limiting children’s opportunities to explore ideas and produce original work independently. Knowledge Gap: There is limited classroom-based evidence on how project-oriented learning combined with open-ended materials can foster creativity among children aged 4–5 years in real educational contexts. Aims: This study aimed to increase the creativity of children aged 4–5 years through the application of Project Based Learning (PjBL) using loose parts media. Results: Using a two-cycle Classroom Action Research design with 13 participants, the proportion of children meeting the success criteria increased from 30.77% in the pre-cycle to 46.15% in Cycle I and 84.62% in Cycle II, measured through indicators of curiosity, ability to produce work, and independence in completing tasks. Novelty: The study demonstrates a structured integration of project-based pedagogy with low-cost, open-ended materials sourced from the environment within an iterative classroom intervention. Implications: The findings suggest that child-centered project activities supported by exploratory materials can provide meaningful learning experiences and serve as a practical approach for fostering creativity in early childhood education settings. Highlights: Progressive gains were observed across cycles, culminating in most participants achieving the target criteria. Engagement increased when exploratory time and stimulating prompts were expanded. Children demonstrated greater autonomy and originality in producing artifacts by the final stage. Keywords: Project Based Learning; Loose Parts; Early Childhood Creativity; Classroom Action Research; Preschool Education